ENGLISH EDUCATION DEPARTMENT STUDENTS’ SPEAKING ANXIETY IN CLASSROOM ACTIVITIES AT UNIVERSITAS MUHAMMADIYAH GRESIK - Ardiyansah, Tri Yuli; Auliya, Prativi Khilyatul (TELL - US JOURNAL, 2023)
The global significance of English is undeniable, especially for students. While learning the language is vital for effective communication, practical usage often remains limited to classroom activities. Surprisingly, English education students also face challenges in practical English communication. Anxiety about making errors leads students to revert to their native language during communication. Language anxiety, in the forms of trait, state, and situation-specific speaking anxiety hampers language mastery. Speaking anxiety particularly affects students especially during presentations and discussions. Addressing this anxiety is crucial for enhancing language skills. By acknowledging this issue, a study was conducted among English education department students at Universitas Muhammadiyah Gresik to identify anxiety triggers and understand strategies for effective English communication. Interview was conducted to explore students’ experiences, emotions, and cognitive processes related to speaking anxiety. The findings unveiled speaking anxiety experienced by students in classroom activities, uncovering the complex interplay of trait and state anxiety as well as situation-specific anxiety. Students’ diverse experiences, thoughts, and triggers shaped anxiety levels, revealing the intricate interplay of cognitive, situational, and individual factors in speaking anxiety. From impromptu to rehearsed speeches, students’ experiences of state anxiety fluctuated, while coping strategies like deep breathing and positive self-talk play a crucial role. Effective preparation and cognitive strategies emerged as valuable tools in managing anxiety. The variety of strategies employed reflects students’ adaptive skills in handling anxiety-inducing situations. This study illuminated the intricate aspects of speaking anxiety and the dynamic strategies students use to navigate the speaking anxiety challenges in classroom activities.